Herança da tolerância da soja ao cowpea mild mottle virus - Arrabal Arias, Carlos A.; Almeida, Alvaro M. R.; Mituti, Tatiana [UNESP]; Kitajima, Elliot W. (FapUNIFESP (SciELO), 2015)
Soybean stem necrosis is caused by Cowpea mild mottle virus (CPMMV) and it has been recognized as an emerging and economically important disease in Brazil. No resistant, but only tolerant cultivars have been identified so far, and their genetic control is still unknown. To investigate the inheritance of soybean tolerance to CPMMV, two crosses between tolerant cultivars (BRS 133 x BRSMT Pintado), and between a susceptible (CD 206) and a tolerant cultivar (BRSMT Pintado) were carried out to obtain F2 and F2:3 generations. Quantitative and qualitative analyses applied to the data from greenhouse evaluations showed that there are at least two distinct major genes determining tolerance to CPMMV, one in the soybean cultivar BRS 133 and another in the cultivar BRSMT Pintado, with predominance of additive genetic effects and heritability levels that allow for efficient selection based on early generation means.
Inheritance of tolerance to cowpea mild mottle virus in soybean
Keywords: Breeding; CPMMV; Glycine max; Tolerance gene; Virus tolerance